NON-THERMAL EMISSION FROM CATACLYSMIC VARIABLES: IMPLICATIONS ON ASTROPARTICLE PHYSICS - Vojtech Šimon (Acta Polytechnica, 2013)
We review the lines of evidence that some cataclysmic variables (CVs) are the sources of non-thermal radiation. It was really observed in some dwarf novae in outburst, a novalike CV in the high state, an intermediate polar, polars, and classical novae (CNe) during outburst. The detection of this radiation suggests the presence of highly energetic particles in these CVs. The conditions for the observability of this emission depend on the state of activity, and the system parameters. We review the processes and conditions that lead to the production of this radiation in various spectral bands, from gamma-rays including TeV emission to radio. Synchrotron and cyclotron emissions suggest the presence of strong magnetic fields in CV. In some CVs, e.g. during some dwarf nova outbursts, the magnetic field generated in the accretion disk leads to the synchrotron jets radiating in radio. The propeller effect or a shock in the case of the magnetized white dwarf (WD) can lead to a strong acceleration of the particles that produce gamma-ray emission via pi0 decay; even Cherenkov radiation is possible. In addition, a gamma-ray production via pi0 decay was observed in the ejecta of an outburst of a symbiotic CN. Nuclear reactions during thermonuclear runaway in the outer layer of the WD undergoing CN outburst lead to the production of radioactive isotopes; their decay is the source of gamma-ray emission. The production of accelerated particles in CVs often has episodic character with a very small duty cycle; this makes their detection and establishing the relation of the behavior in various bands difficult.